-3(8r+6)+4(5r+2)=0

Simple and best practice solution for -3(8r+6)+4(5r+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(8r+6)+4(5r+2)=0 equation:


Simplifying
-3(8r + 6) + 4(5r + 2) = 0

Reorder the terms:
-3(6 + 8r) + 4(5r + 2) = 0
(6 * -3 + 8r * -3) + 4(5r + 2) = 0
(-18 + -24r) + 4(5r + 2) = 0

Reorder the terms:
-18 + -24r + 4(2 + 5r) = 0
-18 + -24r + (2 * 4 + 5r * 4) = 0
-18 + -24r + (8 + 20r) = 0

Reorder the terms:
-18 + 8 + -24r + 20r = 0

Combine like terms: -18 + 8 = -10
-10 + -24r + 20r = 0

Combine like terms: -24r + 20r = -4r
-10 + -4r = 0

Solving
-10 + -4r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -4r = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -4r = 0 + 10
-4r = 0 + 10

Combine like terms: 0 + 10 = 10
-4r = 10

Divide each side by '-4'.
r = -2.5

Simplifying
r = -2.5

See similar equations:

| (-3)-(-8)=-5 | | 10(8)+14= | | 18=y-3 | | 5x-2y=16 | | 2(x-5)+6x/5=4x-2 | | -1/4+3X=11/4 | | X*2+4x+4=0 | | 18.3+32=x | | 4(2a-1)=3(a+4) | | 5x-23=x+x+32 | | 3x-23=32 | | 2v+3-6=14 | | 3|3x+4|-7=5 | | 32d-1=21 | | 7(5-7)=7u | | -6|h-4|=24 | | x-10=/6 | | 37+m=41 | | 7x+7x+2+5x+7=180 | | 20x+15+20(x-1)+15(x-1)=245 | | 3x+2(1-x)=4 | | 2x+1=11x+55 | | x^3-4x^2-25x+28=0 | | 5n+19=2n+52 | | 5n+19=2n | | 4-ax=a-7x | | 132-3x=24x+18 | | 7.6x-4.9x=54 | | 5x^2-27x-18=0 | | C=37.86+0.25 | | t=8+6 | | 2(x+4)-4(1-2x)=0 |

Equations solver categories